Access to Nitriles from Aldehydes Mediated by an Oxoammonium Salt1. (9th February 2015) - Kelly, Christopher B.; Lambert, Kyle M.; Mercadante, Michael A.; Ovian, John M.; Bailey, William F.; Leadbeater, Nicholas E.
Abstract: A scalable, high yielding, rapid route to access an array of nitriles from aldehydes mediated by an oxoammonium salt (4‐acetylamino‐2, 2, 6, 6‐tetramethylpiperidine‐1‐oxoammonium tetrafluoroborate) and hexamethyldisilazane (HMDS) as an ammonia surrogate has been developed. The reaction likely involves two distinct chemical transformations: reversible silyl‐imine formation between HMDS and an aldehyde, followed by oxidation mediated by the oxoammonium salt and desilylation to furnish a nitrile. The spent oxidant can be easily recovered and used to regenerate the oxoammonium salt oxidant.